1999
DOI: 10.1073/pnas.96.14.7922
|View full text |Cite
|
Sign up to set email alerts
|

Five-transmembrane domains appear sufficient for a G protein-coupled receptor: Functional five-transmembrane domain chemokine receptors

Abstract: The putative seven-transmembrane (TM) domains have been the structural hallmark for the superfamily of heterotrimeric G protein-coupled receptors (GPCRs) that regulate a variety of cellular functions by mediating a large number of extracellular signals. Five-TM GPCR mutants of chemokine receptor CCR5 and CXCR4, the Nterminal segment of which connected directly to TM3 as a result of a deletion of TM1-2 and the first intracellular and extracellular loops, have been obtained in this study. Laser confocal microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 27 publications
5
55
0
1
Order By: Relevance
“…According to the global toggle switch model, activation of seven TM receptors requires an inward movement of TM6 and TM7 toward the inner face of TM3 (Schwartz et al 2006). Consistent with this view, it is interesting to note that truncated chemokine receptors with five TM motifs lacking TM1 and TM2 act as fully functional GPCRs (Ling et al 1999). Moreover, receptor mutation analysis of GHSR and GPR39 indicates that TM6 and TM7 are essential for the constitutive receptor activity, further supporting the hypothesis that lacking in TM6 and TM7 2, midbrain; 3, hindbrain; 4, medulla; 5, pituitary; 6, hypothalamus; 7, intestine; 8, stomach; 9, muscle; 10, liver; 11, testis; 12, ovary; 13, gill filament; 14, heart; 15, adipose tissue; 16, kidney; 17, spleen; 18, negative control. has led to the inability of the truncated receptors in activating the signaling events ).…”
Section: Functional Study Of the Two Sbgpr39 Transcriptsmentioning
confidence: 55%
“…According to the global toggle switch model, activation of seven TM receptors requires an inward movement of TM6 and TM7 toward the inner face of TM3 (Schwartz et al 2006). Consistent with this view, it is interesting to note that truncated chemokine receptors with five TM motifs lacking TM1 and TM2 act as fully functional GPCRs (Ling et al 1999). Moreover, receptor mutation analysis of GHSR and GPR39 indicates that TM6 and TM7 are essential for the constitutive receptor activity, further supporting the hypothesis that lacking in TM6 and TM7 2, midbrain; 3, hindbrain; 4, medulla; 5, pituitary; 6, hypothalamus; 7, intestine; 8, stomach; 9, muscle; 10, liver; 11, testis; 12, ovary; 13, gill filament; 14, heart; 15, adipose tissue; 16, kidney; 17, spleen; 18, negative control. has led to the inability of the truncated receptors in activating the signaling events ).…”
Section: Functional Study Of the Two Sbgpr39 Transcriptsmentioning
confidence: 55%
“…This N-terminally truncated OR would start like intact OR with an extracellular domain. For chemokine receptors, which are also G-protein-coupled 7-TM receptors, it has been demonstrated that the five distal TM regions may be sufficient for signal transduction (37). Because 10 of the HLAlinked OR genes comprise the respective splice site as well as the alternative start codon at position 79 (6), one may expect a biological function also for the truncated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-␤-arrestin polyclonal antibody was produced in our laboratory as described (27). Full-length CXCR4 and ␤-arrestin2 clones were generated as described (28). T140 is a generous gift from Dr. Stephen C. Peiper (Dept.…”
Section: Methodsmentioning
confidence: 99%
“…Stable clones were selected and maintained in G418 (800 g/ml). For transient transfection, HEK293 cells were transfected by using the calcium phosphate-DNA co-precipitation method as described previously (28).…”
Section: Methodsmentioning
confidence: 99%